Systemic Amyloid A Amyloidosis in Island Foxes (Urocyon littoralis): Severity and Risk Factors. (May 2016) - Gaffney, P. M.; Witte, C.; Clifford, D. L.; Imai, D. M.; O'Brien, T. D.; Trejo, M.; Liberta, F.; Annamalai, K.; Fändrich, M.; Masliah, E.; Munson, L.; Sigurdson, C. J.
Systemic amyloid A (AA) amyloidosis is highly prevalent (34%) in endangered island foxes ( Urocyon littoralis ) and poses a risk to species recovery. Although elevated serum AA (SAA) from prolonged or recurrent inflammation predisposes to AA amyloidosis, additional risk factors are poorly understood. Here we define the severity of glomerular and medullary renal amyloid and identify risk factors for AA amyloidosis in 321 island foxes necropsied from 1987 through 2010. In affected kidneys, amyloid more commonly accumulated in the medullary interstitium than in the glomeruli (98% [ n = 78 of 80] vs 56% [ n = 45], respectively; P < .0001), and medullary deposition was more commonly severe (19% [ n = 20 of 105]) as compared with glomeruli (7% [ n = 7]; P = .01). Univariate odds ratios (ORs) of severe renal AA amyloidosis were greater for short- and long-term captive foxes as compared with free-ranging foxes (ORs = 3.2, 3.7, respectively; overall P = .05) and for females as compared with males (OR = 2.9; P = .05). Multivariable logistic regression revealed that independent risk factors for amyloid development were increasing age class (OR = 3.8; P < .0001), San Clemente Island subspecies versus San Nicolas Island subspecies (OR = 5.3; P = .0003), captivity (OR = 5.1; P = .0001), and nephritis (OR = 2.3; P = .01). The increased risk associated with the San Clemente subspecies or captivity suggests roles for genetic as well as exogenous risk factors in the development of AA amyloidosis.